2017
DOI: 10.1080/10717544.2017.1303855
|View full text |Cite
|
Sign up to set email alerts
|

Design of a novel curcumin-soybean phosphatidylcholine complex-based targeted drug delivery systems

Abstract: Recently, the global trend in the field of nanomedicine has been toward the design of combination of nature active constituents and phospholipid (PC) to form a therapeutic drug-phospholipid complex. As a particular amphiphilic molecular complex, it can be a unique bridge of traditional dosage-form and novel drug delivery system. In thisarticle, on the basis of drug-phospholipid complex technique and self-assembly technique, we chose a pharmacologically safe and low toxic drug curcumin (CUR) to increase drug-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Thus, the pH-responsive dual-drug release pattern of MTX-Imine-M-CUR might be facilitated to reduce the burst release and leakage of the drug. 17,41 In vitro cellular uptake CUR and M-CUR for the same incubation time ( Figures 3A and 4A). This result indicates the manner of time-dependent cellular uptake of CUR molecules and CUR-loaded nanoparticles.…”
Section: In Vitro Drug Releasementioning
confidence: 94%
See 2 more Smart Citations
“…Thus, the pH-responsive dual-drug release pattern of MTX-Imine-M-CUR might be facilitated to reduce the burst release and leakage of the drug. 17,41 In vitro cellular uptake CUR and M-CUR for the same incubation time ( Figures 3A and 4A). This result indicates the manner of time-dependent cellular uptake of CUR molecules and CUR-loaded nanoparticles.…”
Section: In Vitro Drug Releasementioning
confidence: 94%
“…After filtration by a 0.22 µm filter membrane, a part of the filtrate was analyzed for the determination of drug loading content by a high-performance liquid chromatography method as described in our previous studies. 17,41 The drug loading content of MTX-Imine-M-CUR was calculated as (amount of drug in MTX-Imine-M-CUR)/ (weight of MTX-Imine-M-CUR) ×100%.…”
Section: Drug Loading Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results proved the presence of hydrogen bonds interaction between curcuminoids and polar head of HEPC coupled with insertion of cholesterol into the membranes of Curs-Phyto which led to the physicochemical stability of phytosomal nanoparticles. 25,30 This might be facilitated for the enhancement in cellular uptake of Curs-Phyto via oral administration. In vitro drug release profiles Figure 6 showed the in vitro drug release profiles of Curs-Phyto separately calculated for Cur, DMC and BDMC.…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 99%
“…The similar structure component and high affinity between the phospholipid on the phytosome Curs-Phyto's surface phospholipid and cell membranes are crucial determinants. 30 Phytosome can easily move from a hydrophilic environment into the lipophilic environment of the cell membrane and then enter the cell. 33 Our data demonstrated that Curs-Phyto exhibited higher association and internalization into the cells compared to that of free curcuminoids, which proved that the phytosomal formulation has a profound impact on the uptake of curcuminoids.…”
Section: Cell Cycle Analysismentioning
confidence: 99%